2015
DOI: 10.1007/s13246-015-0353-6
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of image distortion and CT number accuracy within a wide-bore CT extended field of view

Abstract: Although wide bore computed tomography (CT) scanners provide increased space for patients, the scan field of view (sFOV) remains considerably smaller than the bore size. Consequently, patient anatomy which spans beyond the sFOV is truncated and the information is lost. As a solution, some manufacturers provide the capacity to reconstruct CT images from a partial dataset at an extended field of view (eFOV). To assess spatial distortion within this eFOV three phantoms were considered a 30 x 30 x 20 cm 3 slab of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 15 publications
(24 reference statements)
0
10
0
Order By: Relevance
“…In cases where patient anatomy extends past the scan field of view (FOV), it is necessary to account for the missing tissue in the CT image. Extended field‐of‐view (eFOV) reconstruction algorithms attempt to recreate the original patient geometry that extends past the original scan window . However, these reconstruction techniques may result in artifacts that can distort the image intensities and patient external contours which can produce inaccurate calculation of the treatment beam attenuation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In cases where patient anatomy extends past the scan field of view (FOV), it is necessary to account for the missing tissue in the CT image. Extended field‐of‐view (eFOV) reconstruction algorithms attempt to recreate the original patient geometry that extends past the original scan window . However, these reconstruction techniques may result in artifacts that can distort the image intensities and patient external contours which can produce inaccurate calculation of the treatment beam attenuation.…”
Section: Introductionmentioning
confidence: 99%
“…Extended field-of-view (eFOV) reconstruction algorithms attempt to recreate the original patient geometry that extends past the original scan window. [10][11][12][13][14][15][16][17] However, these reconstruction techniques may result in artifacts that can distort the image intensities and patient external contours which can produce inaccurate calculation of the treatment beam attenuation. The purpose of this study is to determine the accuracy of the CT HU numbers and external body contour and to quantify the resulting change in radiation dose calculations for three different eFOV reconstructions algorithms implemented on Siemens CT scanners.…”
Section: Introductionmentioning
confidence: 99%
“…Results from the current study are consistent with these findings. Another group used anthropomorphic phantoms to study image distortion and CT number accuracy of a wide-bore CT scanner, and found similar results [8]. As suggested by a previous study [19], the dosimetric accuracy of treatment plans can reasonably be assumed to be within ±4% of target dose for all treatment sites in a worst-case scenario if the CT number variations are within ±100 HU of its standard value.…”
Section: Figmentioning
confidence: 66%
“…Significant variation in both CT number accuracy and image distortion have been reported as a function of phantom displacement outside the sFOV [3,7,8], which could affect the dosimetric accuracy of the treatment plan created with these images. The extent and impact of dose discrepancies vary among systems, and the uncertainties involved have made some users reluctant to use HD FOV or eFOV.…”
Section: Introductionmentioning
confidence: 99%
“…The more traditionally customizable CT scan parameters such as kilovoltage, current, resolution, slice thickness, field-of-view (FOV) and reconstruction algorithm, have been more heavily studied in terms of the induced HU changes and subsequent impact on dose calculation. [10][11][12][13][14][15][16][17][18][19] These options can be varied through the selection of various anatomic scan protocols pre-installed onto the scanner. In addition, there is also a large variety of reconstruction kernel options available from the manufacturer to choose from.…”
Section: Introductionmentioning
confidence: 99%